Analysis of Indonesian Government Public Communication based on Image Restoration Theory - Aldy Ridwan Sukarsa; Octaviana Setya Devi (Institute of Computer Science (IOCS), 2021)
The spread of Covid-19 virus in all around the world has been happening so fast and massive. In addition, this corona virus has gotten a multidimensional crisis in the world. All countries are working hard to fight the spread of the virus either from medical side or country's policy. In Indonesia was the corona virus detected and confirmed after 4 months from the 1st case in Wuhan on November 2019. Along that 4-month period, many questions were being inquired by Indonesian legislative members about the spread of this corona virus. This journal discusses the analysis of public communication which has been performed by the Indonesian government in the face of the spreading of this Covid-19 from February to April 2020. This journal utilizes communication research which focuses on Image Restoration Theory (TIR), providing strategy in restoring image by denying strategy, evading responsibility strategy, deducting offense, corrective action and shouldering the crisis impact. he result of this research discovers that government has not been optimal to undergo the manual of crisis communication in common way, starting from confused communication message, inconsistent declaration, awkward use of social media. Eventually, government has not involved the stakeholders maximally.